Ander weë tot God? Calvyn oor nie-Christelike godsdienste - P. C. Potgieter (Acta Theologica)
Religious freedom is currently guaranteed by constitution in many countries. At the same time it has become a popular notion that no religion should claim to be the only true way to knowledge of God. In the sixteenth century Christianity was far less tolerant of aberrations and false religion. This study explores John Calvin’s views on the religion of Gentiles (paganism), Turks (Islam), and Jews (Judaism). Calvin refers to these religions not only in the consecutive editions of his Institutes, but also in a number of other writings. He asserts the uniqueness of Christ as the only Mediator and Redeemer for mankind on his unconditional acceptance of Holy Scriptures as the Word of God. As God created man in his own image with a distinct sensus divinitatis, the offer of true knowledge of  God remains open to anyone.